2015
DOI: 10.1017/s0007114515004055
|View full text |Cite|
|
Sign up to set email alerts
|

General and abdominal adiposity in a representative sample of Portuguese adults: dependency of measures and socio-demographic factors’ influence

Abstract: The aims of this study were: (i) to estimate the dependency between BMI and waist:height ratio (WHtR) as measures of general and abdominal adiposity, and (ii) to evaluate the influence of socio-demographic factors on both measures and on their dependency in risk classification. Data from a cross-sectional study conducted in 2009 among a representative sample of 3529 Portuguese adults were used. Height, weight and waist were measured and socio-demographic data (sex, age, education level, occupational status, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
5
11
1
Order By: Relevance
“…In our study, the prevalence of abdominal obesity differed greatly depending on the criteria used, with 28% when WC was considered, and much higher (58.4%) using WHtR. These figures are slightly higher than those recently found among Portuguese population (42.1% of adults with high WHtR) [ 33 ] but similar to those found in other Spanish groups, which also observed the same discrepancy between these two indicators [ 4 ]. For example, Rodríguez-Rodríguez et al [ 5 ] found 22.2% abdominal obesity considering WC as a reference and 54.7% using WHtR ≥ 0.5.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our study, the prevalence of abdominal obesity differed greatly depending on the criteria used, with 28% when WC was considered, and much higher (58.4%) using WHtR. These figures are slightly higher than those recently found among Portuguese population (42.1% of adults with high WHtR) [ 33 ] but similar to those found in other Spanish groups, which also observed the same discrepancy between these two indicators [ 4 ]. For example, Rodríguez-Rodríguez et al [ 5 ] found 22.2% abdominal obesity considering WC as a reference and 54.7% using WHtR ≥ 0.5.…”
Section: Discussionsupporting
confidence: 81%
“…In developing countries, the prevalence of obesity is usually higher in the female population, whereas the trend in developed countries varies [ 32 ]. For example, in Portugal [ 33 ], the Netherlands [ 34 ], and Bulgaria [ 35 ], the prevalence of overweight and obesity is higher among males, as in our study, while in Poland [ 2 ] it is higher among females. However, the results of other studies conducted in Spain show a variable trend: the 2012 ENRICA study showed that obesity affects up to 23,1% of men and 16.3% of women between 18 and 64 years of age [ 21 ]; the DORICA (Dyslipidemia, Obesity and Cardiovascular Risk in Spain) study noted that the prevalence of obesity was higher in women than men (17.5% versus 13.2%) [ 36 ]; and a study by Rodríguez-Rodríguez et al [ 5 ] found no differences in the prevalence of obesity according to sex, although the prevalence of overweight was higher among men.…”
Section: Discussionsupporting
confidence: 70%
“…It is used to describe greater adiposity as compared to excess body weight relative to height, although it does not depict regional body adiposity distribution (Wells 2010;Mondal and Sen 2014). There is a large amount of scientific literature on the assessment of overweight and obesity among adult using this anthropometric index and here the recent studies of Das and Bose (2006), Sarkar et al (2009), Chopra et al (2013), , Shafaghi et al (2014), Anuradha et al (2015), Rengma et al (2015) and Kowalkowska et al (2016) are mentionable. It is now an established fact that a BMI value of ≥25.00 kg m −2 is a major risk factor for a wide range of metabolic diseases such as cardio-vascular diseases (Mandviwala et al 2016), hypertension (Kelly et al 2015), type II diabetes (Bhowmik et al 2014) and certain types of cancers (Argolo et al 2015).…”
Section: Introductionmentioning
confidence: 96%
“…This complex envi-ronment consists of genetic (Sitek et al 2014;Rosset et al 2016), socio-economic (Chung et al 2016;Kowalkowska et al 2016), nutritional (Gurnani et al 2015;Binks 2016) and psychological (Czegledi 2016; Kelley et al 2016) factors. Obesity is becoming a major public health issue in both the developed and developing countries as it contributes to numerable preventable, non-communicable diseases and related mortalities and morbidities (Huxley et al 2010;Misra and Khurana 2011;WHO 2011;Akin and Nienaber 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It was described in a recent study that high general adiposity is more frequent in men than in women and in older age groups. 12 Different populations may have different genetic, social, geographic characteristics, as well as different levels of food availability, physical activities and other influences relevant to the development of obesity. It is not easy to arrive at conclusions that are the same for all populations.…”
Section: ■ Discussionmentioning
confidence: 99%